La cultura tributaria y su efecto en el cumplimiento de las obligaciones tributarias en las pequeñas empresas comerciales de la ciudad de Riobamba, periodo 2019. aplicación de la regresión lineal - Vanessa Estefanía, Alvarez Verdezoto (2021)
ABSTRACT: The research objective is to determine the effect of the tax culture on compliance with tax obligations in small commercial companies in the city of Riobamba. The study is correlational and explanatory; its design uses quantitative, descriptive, and probabilistic analysis techniques. The research is developed in three well-defined phases: Phase 1. Bibliographic research; Phase 2. Diagnosis of owners of small commercial companies in Riobamba, the sample was 75 merchants; and, Phase 3. Diagnosis of experts in the tax field for which there was a sample of 14 professional accountants understood the tax issue. The surveys collected information on characteristics, tax culture, and its effect on tax obligations in small commercial companies in Riobamba. Among the most important results, it was determined that 78.6% of experts mention that merchants are dissatisfied, not very satisfied, and moderately satisfied with the tax culture. Finally, it was concluded that the tax culture has a significant effect on compliance with tax obligations in small commercial companies in Riobamba. Chapter 1, the referential framework was developed, where the problem under study was analyzed, general and specific problems were raised, and the objectives and research hypotheses. Chapter 2, the theoretical framework that supports the research, was developed, where the theoretical foundation of the study variables and indicators is explained. Chapter 3 presents the methodological framework that guides the research work and identifies the population and sample under study. Chapter 4 presents the results presented in tables and graphs containing the corresponding frequencies, percentages, and analyzes. Finally, the discussion is carried out, the study's hypotheses are checked, and the investigation's conclusions and recommendations were obtained. KEY WORDS: culture, cognitive, affective, behavioral, collection, normativity. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258